The extent of medical service providers’ knowledge of health quality standards in Buraidah Central Hospital in Al-Qassim - Al-Mutairi, Nayef Sultan (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to know the extent of medical service providers’ knowledge of health quality standards in Buraidah Central Hospital in Al-Qassim, by identifying the reality of health quality standards in Buraidah Central Hospital in Qassim. And presenting proposals to increase the education of the medical services’ practitioners to the health quality standards, and the study used the descriptive analytical approach to identify the study goals, and the study community consisted of medical service providers working in Buraidah Central Hospital, and a sample questionnaire consisted of (116) medical providers in Buraidah Central Hospital In Al-Qasim, the questionnaire was a study tool for collecting its data, and the data was analyzed using SPSS to analyze the study data. The study reached a number of results, the most important of which is the presence of a positive (positive) and statistically significant relationship at the level of significance (0.01) between medical service providers’ knowledge of health quality standards and the quality of health services, where the value of the Pearson coefficient (0.751) and a strong direct value. In light of the results.